Bermudagrass Production in Florida - Carrol G. Chambliss; F. A. Johnson; Martin B. Adjei (EDIS)
This document is SS-AGR-60, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date April 2000. This is a minor revision by Martin Adjei of the June 2002 version of the same title. Revised February 2006.